Correction to: Telemedicine in general neurology: use of audiovisual consultation for on call back-up service in an acute care hospital - Janssen, Frank; Awadallah, Mohammed; Alhalabi, Awed; Koerber, Barbara; Lang, Reinhard; Scibor, Mateusz; Handschu, Rene (Journal of Neurology, 2019)
The original version of this article unfortunately contained a mistake in the acknowledgement section.
EVALuna2:206748